Turning points of transition in agriculture - Jelić Sreten; Jovanović Tatjana (Sociološki Pregled, 2010)
In our paper we indicate significant items of transition process in Serbian agriculture. Particular attention is given to ownership structure of husbandry of South-east Europe countries, quantity of nonarable land and problems of privatization husbandry members are facing with. We also pointed out experiences of EU members, which could be useful for Serbian agriculture. All analyses are made on basis of relevant databases and available literature.